2018
DOI: 10.1530/erc-18-0025
|View full text |Cite
|
Sign up to set email alerts
|

Role of the tumor microenvironment in digestive neuroendocrine tumors

Abstract: Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) represent a group of heterogeneous tumors whose incidence increased over the past few years. Around half of patients already present with metastatic disease at the initial diagnosis. Despite extensive efforts, cytotoxic and targeted therapies have provided only limited efficacy for patients with metastatic GEP-NETs, mainly due to the development of a certain state of resistance. One factor contributing to both the failure of systemic therapies and the eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 194 publications
2
13
0
Order By: Relevance
“…This observation is in accordance with the accumulating literature that attempts to unravel the immune landscape of PNENs and which reports a presence of TILs within the tumor microenvironment of PNENs, but mostly in very small numbers [41][42][43]. In addition, the loss of expression of MHC I class molecules and altered expression of immunomodulatory factors has been reported in PNENs and might allow them to evade control of the immune system [41,42]. Several of the master regulator proteins, differentially expressed proteins with an important role in tumorigenesis, that were identified by Alvarez et al in gastroenteropancreatic NENs (GEP-NENs) were immunomodulatory factors [44].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is in accordance with the accumulating literature that attempts to unravel the immune landscape of PNENs and which reports a presence of TILs within the tumor microenvironment of PNENs, but mostly in very small numbers [41][42][43]. In addition, the loss of expression of MHC I class molecules and altered expression of immunomodulatory factors has been reported in PNENs and might allow them to evade control of the immune system [41,42]. Several of the master regulator proteins, differentially expressed proteins with an important role in tumorigenesis, that were identified by Alvarez et al in gastroenteropancreatic NENs (GEP-NENs) were immunomodulatory factors [44].…”
Section: Discussionsupporting
confidence: 91%
“…In general, a low percentage of TILs (≤5%) was observed with only three samples that had a percentage of TILs between 5% and 30%. This observation is in accordance with the accumulating literature that attempts to unravel the immune landscape of PNENs and which reports a presence of TILs within the tumor microenvironment of PNENs, but mostly in very small numbers [41][42][43]. In addition, the loss of expression of MHC I class molecules and altered expression of immunomodulatory factors has been reported in PNENs and might allow them to evade control of the immune system [41,42].…”
Section: Discussionsupporting
confidence: 91%
“…Such factors are increasingly appreciated to be implicated in pharmacological treatment efficacy/resistance, tumour aggressiveness, proclivity to metastasis and tumour growth. These have been extensively reviewed elsewhere [78,79].…”
Section: The Tumour Microenvironmentmentioning
confidence: 99%
“…By virtue of their expression of pro-angiogenic factors, including but not limited to VEGF, platelet-derived growth factor, fibroblast growth factor and angiopoietin-2 (more so in PanNEN) [78], NETs are highly vascularised, with a microvasculature network up to an order of magnitude denser than that observed in epithelial neoplasms. The "neoangiogenic switch" may be related to tumour-infiltrating immune cells, but this requires further investigation.…”
Section: The Tumour Microenvironmentmentioning
confidence: 99%
“…The tumor cell microenvironment includes tumor cells and other cells, such as fibroblasts, lymphocytes, macrophages, adipocytes, and other secreted factors, to form a unique tumor microenvironment system. An abnormal imbalance of the cell microenvironment often leads to tumorigenesis (16). It is suggested that molecules related to metabolic syndrome can accelerate the progression of endometrial cancer not only by acting directly on tumor cells but also by further remodeling the immune microenvironment of tumors.…”
Section: Introductionmentioning
confidence: 99%